Comparison of efficacy of anti-diabetics on non-diabetic NAFLD: A network meta-analysis - Jin, Dachuan; Cui, Zhongfeng; Jin, Shunqin; Zhou, Tao; Guo, Baoqiang; Gao, Peng; Li, Guangming (Frontiers in Pharmacology, 2023)
This study aimed to assess the efficacy of currently used anti-diabetic medications in the treatment of non-alcoholic fatty liver disease (NAFLD) without diabetes. DESIGN: The efficacy of various anti-diabetic medicines on non-alcoholic fatty liver disease in the absence of diabetes was evaluated by searching Pubmed, Embase, Cochrane Library, and Web of Science for randomized controlled trials (RCT) only. The methodological quality was evaluated using the Cochrane bias risk assessment tool, and the data were analyzed using Stata software (version 15.1). Results: All papers published between the time of the pooling and September 2022 were searched. There were a total of 22 randomized controlled studies with a total sample size of 1355 cases. The outcomes of interest included variations in alanine transaminase (ALT) and aspartate transaminase (AST). Rosiglitazone (SUCRA: 100%) and vildagliptin (SUCRA:99.9%) were the best anti-diabetic medicines to improve ALT and AST, respectively, in patients with NAFLD without diabetes, according to the findings of this network meta-analysis. Conclusion: In accordance with the Network Ranking plot, Rosiglitazone was the best anti-diabetic medicine for improving ALT, and vildagliptin was the best for improving AST in patients with non-diabetic NAFLD.